The Synergy of ‐260T T CD14 and ‐308GG TNF‐α Genotypes in Survival of Critically Ill Patients. (26th December 2012) - Fallavena, P. R. V.; de Jesus Borges, T.; Paskulin, D. D.; Thurow, H. S.; de Oliveira Paludo, F. J.; dos Santos Froes, C.; Graebin, P.; Dias, F. S.; de Toledo Nóbrega, O.; Alho, C. S.
Abstract: Literature suggests that the analysis of several polymorphic genetic markers is more informative than the analysis of a single polymorphism. In this study, we tested whether the shared inheritance of TLR2 and TLR4 and TNF‐α allelic variants may act in synergy with ‐260C>T CD14 SNP on the outcome from critical conditions. We monitored 524 critically ill patients from South Brazilian, daily from the ICU admission to their discharge from hospital, or death. Our results revealed that TLR2, TLR4 or TNF‐α SNPs alone did not show a significant role in the outcome from critical illness. However, when we performed a combined analysis with the CD14 inheritance, we detected a significant higher survivor rate in ‐260TT CD14/ ‐308GG TNF‐α individuals ( P = 0.037). In the adjusted analysis including the main clinical predictors to mortality, we observed that ‐260TT / ‐308GG double‐genotype was a significant protective factor towards survival ( P = 0.046). An increased probability for survival of ‐260TT / ‐308GG was also observed by 'pathway genetic load' analysis (unweighted: P = 0.041; weighted: P = 0.036). When we applied a hazard function analysis with the ‐260TT / ‐308GG variable as a discriminating factor, ‐260TT/‐308GG patients group had, in fact, a higher survivor rate ( P = 0.024). Connected to the beneficial effect of ‐260TT CD14, the ‐308GG TNF‐α genotype was protective against the reported over expression of TNF‐α caused by ‐308A rare allele. Results support the hypothesis that the interaction between ‐260C>T CD14 and ‐308G>A TNF‐α functional SNPs may be synergistically influencing the outcome of critically ill patients.